2017
DOI: 10.1101/gr.224436.117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of regulatory variation across human iPSCs and differentiated cells

Abstract: Induced pluripotent stem cells (iPSCs) are an essential tool for studying cellular differentiation and cell types that are otherwise difficult to access. We investigated the use of iPSCs and iPSC-derived cells to study the impact of genetic variation on gene regulation across different cell types and as models for studies of complex disease. To do so, we established a panel of iPSCs from 58 well-studied Yoruba lymphoblastoid cell lines (LCLs); 14 of these lines were further differentiated into cardiomyocytes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 66 publications
(81 reference statements)
10
101
0
Order By: Relevance
“…Of particular interest is the impairment of EMT in patient cells; while likely to derive from the delayed differentiation, undergoing an EMT is absolutely essential during neural crest As might be expected, we observed considerably more differences between cell lines at the differentiated iNCC stage than at the pluripotent stage, with less clustering between the mother and patient lines in the PCA analysis of RNA-Seq data and more differentially expressed and mis-spliced genes, suggesting that the effects of the TXNL4A variants in the patients are magnified upon differentiation to iNCCs. This finding is in agreement with previous work which has shown greater disparity between disease-affected and diseaseunaffected differentiated cells than iPSCs [85,86]. This observation would also go some way in explaining the tissue-specificity of BMKS; if NCCs are particularly sensitive to changes in TXNL4A expression and show the greatest functional and transcriptomic differences of all cell types, then it would be logical that the tissues derived from the NCCs would be the most affected phenotypically.…”
Section: Discussionsupporting
confidence: 91%
“…Of particular interest is the impairment of EMT in patient cells; while likely to derive from the delayed differentiation, undergoing an EMT is absolutely essential during neural crest As might be expected, we observed considerably more differences between cell lines at the differentiated iNCC stage than at the pluripotent stage, with less clustering between the mother and patient lines in the PCA analysis of RNA-Seq data and more differentially expressed and mis-spliced genes, suggesting that the effects of the TXNL4A variants in the patients are magnified upon differentiation to iNCCs. This finding is in agreement with previous work which has shown greater disparity between disease-affected and diseaseunaffected differentiated cells than iPSCs [85,86]. This observation would also go some way in explaining the tissue-specificity of BMKS; if NCCs are particularly sensitive to changes in TXNL4A expression and show the greatest functional and transcriptomic differences of all cell types, then it would be logical that the tissues derived from the NCCs would be the most affected phenotypically.…”
Section: Discussionsupporting
confidence: 91%
“…We next turned our attention to differences in the magnitude of variation in gene expression levels across time points, within and between species. Previous studies reported that variation in gene expression levels between individuals was lower in iPSCs than in differentiated cells ([ 22 , 23 ] and Additional file 2 : Figure S10A). We were thus interested in gene expression variation during iPSC differentiation in our comparative system.…”
Section: Resultsmentioning
confidence: 94%
“…Whole exome sequencing showed that clonal fibroblasts and iPSCs contained a similar number of mutations with more than 90% of them preexisting randomly in small subsets of the parental unselected fibroblast population as evidenced by deep, targeted resequencing. While there is plenty of evidence that common genetic variation [ 121 , 122 , 123 , 124 , 125 , 126 ], and so much more chromosomal aneuploidy, cause molecular heterogeneity in iPSCs, none of the present iPSC-based studies on idiopathic SCZ ( Table 1 ) has applied donor-matched digital (i.e., SNP-based) karyotype maps to detect chromosomal anomalies more precisely. Chromosomal anomalies extent also to copy number alterations, as shown by high resolution karyotype mapping (detection limit > 200 KB) of donor-matched samples [ 124 ].…”
Section: Future Directionsmentioning
confidence: 99%